Relationships between student teachers' self-concepts of student teaching roles and teacher-training instructors' descriptions of student teachers' role enactments - Ycaro, Godofredo L. 1939- (s.n.], 1966)
Measures of student teachers'self-concepts in selected regional public normal schools are provided in this study and teacher training instructors' descriptions of their role enactments are identified. General conclusions of the study show that student teachers as persons, as teachers, and as professional members of the Bicol Teachers College, the Bukidnon Normal School, the Cebu Normal School, the Iloilo Normal School, and the Pangasinan Normal School are similar.